Effects of gradation on hydraulic conductivity properties of compacted laterite soil liner: a review - Yamusa, Bello Yamusa (IJSER, 2016)
This paper presents the recent review on the effects of gradation on hydraulic conductivity properties of compacted laterite soil liner. The distribution of different grain sizes affects the engineering properties of soil such as compressibility, shear strength, and hydraulic conductivity . It is observed that there are variations in hydraulic conductivity values in laterite soils from various researches around tropical countries of the world . Hydraulic conductivity varies from 4.36×10 -3 m/s to 4.7×10 -11 m/s relative to fine contents ranging from 1.3% to 69% and coarse contents ranging from 31% to 98.7%. Generally, there is no clear trend established for effects of gradation on hydraulic conduc- tivity properties of compacted laterite soil liners. This is because laterite soils with less than 50 fines content cannot be used as liner or hydra ulic barriers because their hydraulic conductivities are less than the minimum requirement of 1 × 10 -9 m/s. It is anticipated that with logical understanding of the effects of gradation on hydraulic conductivity properties of compacted laterite soil it wil l serve as a guide in the design of hydraulic barriers for engineered sanitary landfills in tropical countries around the world.